Inducing differentiation of premalignant hepatic cells as a novel therapeutic strategy in hepatocarcinoma - Wolf, Benita; Breuhahn, Kai (Cancer research, 2016)
Hepatocellular carcinoma (HCC) represents the second leading cause of cancer-related deaths and is reported to be resistant to chemotherapy caused by tumor-initiating cells. These tumor-initiating cells express stem cell markers. An accumulation of tumor-initiating cells can be found in 2% to 50% of all HCC and is correlated with a poor prognosis. Mechanisms that mediate chemoresistance include drug export, increased metabolism, and quiescence. Importantly, the mechanisms that regulate quiescence in tumor-initiating cells have not been analyzed in detail so far. In this research we have developed a single cell tracking method to follow up the fate of tumor-initiating cells during chemotherapy. Thereby, we were able to demonstrate that mCXCL1 exerts cellular state-specific effects regulating the resistance to chemotherapeutics. mCXCL1 is the mouse homolog of the human IL8, a chemokine that correlates with poor prognosis in HCC patients. We found that mCXCL1 blocks differentiation of premalignant cells and activates quiescence in tumor-initiating cells. This process depends on the activation of the mTORC1 kinase. Blocking of the mTORC1 kinase induces differentiation of tumor-initiating cells and allows their subsequent depletion using the chemotherapeutic drug doxorubicin. Our work deciphers the mCXCL1-mTORC1 pathway as crucial in liver cancer stem cell maintenance and highlights it as a novel target in combination with conventional chemotherapy. Cancer Res; 76(18); 5550-61. ©2016 AACR.